Understanding Causality Relation among FDI, Foreign Trade and Economic Growth - Saimul Saimul; Arif Darmawan (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
This study aims to analyze the causality relationship between Foreign Direct Investment (FDI), Foreign Trade, and Economic Growth in Indonesia using quarterly time-series data from Q1-2004 to Q2-2019. This study uses co-analytical techniques, VECM integration, and Engle-Granger causality. The results of a two-way causality test happen between export and GDP variables, as well as import and GDP variables. In other words, foreign trade has an essential role in increasing economic growth in Indonesia. However, the two-way causality relationship takes place only in the short term. In the long run, it does not occur; what happens in the long term is an only one-way relationship, namely from foreign trade (X and M) to economic growth. While export and import relations have an only one-way relationship, namely from import growth to export growth, and this relationship only happens in the short term. In contrast, in the long term, it has no significant relationship. Likewise, the one-way relationship also takes place from imports to FDI in the short term. At the same time, export variables and GDP variables do not have a significant relationship with FDI variables. In the long-term economic growth, it turns out to be very instrumental in increasing both FDI, exports, and imports.